Assessment of prognostic factors in long-term survival of male and female patients with colorectal cancer using non-mixture cure model based on the Weibull distribution. (September 2021) - Azizmohammad Looha, Mehdi; Zarean, Elaheh; Masaebi, Fatemeh; Pourhoseingholi, Mohamad Amin; Zali, Mohamad Reza
Abstract: Objective: Colorectal cancer (CRC) is known as one of the malignant form of cells growing in the inner lining of colon and rectum which could seriously affect the cure rate of patients. We aimed to evaluate the effect of prognostic factors on cure fraction of CRC patients. Methods: A total of 1043 CRC patients were included to the study from December 2001 to January 2007 at the Research Center of Gastroenterology and Liver Disease in Shahid Beheshti University of Medical Sciences, Tehran, Iran. Patients' information was extracted from their medical records, then they were followed to identify their death status via phone-call. Weibull non-mixture cure model was used to evaluate the effect of the risk factors on cure fraction of CRC patients. Results: The five-years survival rate was 0.66 (males: 0.64 and female: 0.69). The median survival time for non-cured CRC patients were 3.45 years (males: 3.46; females = 3.45 years). In the single Weibull model, BMI≥30 (OR = 4.61, p-value = 0.033), poorly differentiated tumor grade (OR = 0.36, p-value = 0.036), tumor size≥25 mm (OR = 0.22, p-value = 0.046), and N1-stage (OR = 0.42, p-value = 0.005) had significant effect on females' cure fraction. Also, cure fraction of male CRC patients significantly affected by BMI (levels:25.0–29.9-OR = 12.13-p-value<0.001; ≥30-OR = 7.00-p-value = 0.017), T1-stage (OR = 0.52, p-value = 0.021), M1-stage (OR = 0.45, p-value = 0.007), IV-staging (OR = 0.36, p-value = 0.041) and IBD (OR = 0.26, p-value = 0.017). In multiple Weibull model, females were associated with tumor size≥25 mm (OR = 0.20, p-value = 0.044) and N1-stage (OR = 0.45, p-value = 0.013) and males were affected by M1-stage (OR = 0.41, p-value = 0.011) and IBD (OR = 0.20, p-value = 0.022).The cure fraction of males and females CRC patients was 64% and 69%, respectively. Conclusions: The prognostic factors for cure fraction of patients with CRC may be different among males and females. Further multicenter studies are required to assess the effect of common prognostic factors between males and females. Highlights: Poorly differentiated tumor grade, higher tumor size and N1-stage were affected females' cure fraction. BMI, T1-stage, M1-stage, IV-staging and history of IBD were affected males' cure fraction. The prognostic factors for cure fraction of patients with CRC were different among males and females.